2008
DOI: 10.1371/journal.pntd.0000198
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Previously Undiagnosed Leprosy in the General Population of Northwest Bangladesh

Abstract: BackgroundThe prevalence of previously undiagnosed leprosy (PPUL) in the general population was determined to estimate the background level of leprosy in the population and to compare this with registered prevalence and the known PPUL in different levels of contacts of leprosy patients.Methodology and Principal FindingsMultistage cluster sampling including 20 clusters of 1,000 persons each in two districts with over 4 million population. Physical examination was performed on all individuals. The number of newl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
48
1
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 9 publications
(13 reference statements)
4
48
1
5
Order By: Relevance
“…This state had an annual case detection rate of 20.4/100,000 people in 2008, which is much higher than the Brazilian average of 5.8/100,000 people (MS/SVS 2009), indicating that Mycobacterium leprae is circulating amongst the children in PA. Furthermore, in highly endemic areas, the prevalence of previously undiagnosed leprosy in the general population is six times higher than the registered prevalence (Moet et al 2008).…”
mentioning
confidence: 83%
“…This state had an annual case detection rate of 20.4/100,000 people in 2008, which is much higher than the Brazilian average of 5.8/100,000 people (MS/SVS 2009), indicating that Mycobacterium leprae is circulating amongst the children in PA. Furthermore, in highly endemic areas, the prevalence of previously undiagnosed leprosy in the general population is six times higher than the registered prevalence (Moet et al 2008).…”
mentioning
confidence: 83%
“…As per the latest data available [1], only 1.34 lakh new leprosy cases were reported in India during the year 2009-2010, and leprosy was declared eliminated on January 1, 2006, reaching the level of below 1 (0.98) per 10,000 population in India [2]. However, several reports [2][3][4][5] from Uttar Pradesh and Maharashtra [6,7], India, and also from other countries such as Bangladesh [8] and Brazil [9] had indicated that leprosy case load may be many folds higher in India and elsewhere than as being reported under respective government health systems. This has created doubts [10,11] about the actual achievements on leprosy control.…”
Section: Introductionmentioning
confidence: 99%
“…Quando comparado à população em geral, o maior risco de adoecimento está entre os contatos domiciliares 5 , o que indica que tanto o tipo de hanseníase quanto as distâncias do caso índice são fatores importantes para o risco da doença 6,7,8,9 . Em regiões de alta endemicidade, a vigilância de contatos domiciliares, assim como da população em geral, torna-se uma medida imprescindível, visto que toda a população passa a sofrer algum tipo de exposição 10 .…”
unclassified
“…Os contatos desses pacientes possuem uma chance de quatro a dez vezes maior de se infectarem do que a população em geral 17,27 e a chance de encontrar hanseníase entre diferentes categorias de vizinhos e contatos sociais é entre três e cinco vezes maior 7 . Fatores individuais, condições socioeconômicas desfavoráveis e ambientes que concentram elevado número de pessoas favorecem a transmissão do bacilo 27 .…”
unclassified